Pengaruh Korupsi, Pengeluaran Pemerintah dan Jumlah Uang Beredar (M2) Terhadap Pertumbuhan Ekonomi di ASEAN - Rado Sujidno; Ratu Eva Febriani (Universitas Mataram, 2023)
The researchers want to analysis about Corruption, government spending, money supply (M2), and economic growth. The method of analysis use panel data. The number of cross-section data is 7 countries and time-series data are nine years. The best model was obtained from redundant fixed effect, Correlated random effects-Hausman test, and technical consideration. The selected model is the fixed-effect model. Based on regression output, government spending has a significant negative effect on economic growth in ASEAN. So, government spending can hamper economic growth in ASEAN. While; other variables such as Corruption and money supply (M2) are not significant. Meaning, that Corruption and money supply (M2) do not affect the economic growth in ASEAN.